2005
DOI: 10.1123/jsep.27.2.212
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Anxiety on Motor Performance: A Test of the Conscious Processing Hypothesis

Abstract: The aim of this study was to examine the conscious processing hypothesis as an explanation of the anxiety/performance relationship. The study was designed to identify conscious processing performance effects while controlling for an alternative attentional threshold explanation identified in previous research. Participants completed 60 golf putts. They completed 3 blocks of 10 putts in single task, task-relevant shadowing, and task-irrelevant tone-counting conditions. Each set of 3 × 10 putts was completed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 0 publications
3
96
1
3
Order By: Relevance
“…This rhythm was also studied as a marker of resources allocation during motor programming 32 . Beta oscillation (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30),on the other hand, has a central position in the treatment of sensorimotor information and serves as a functional link between different brain regions such as the pre-motor, motor (M1), and somatosensory (S1) cortex, the supplementary motor area, and the cerebellum 31 . Beta oscillation could play the role of a motor "binding" linking the different commands related to a global gesture as suggested for sensory awareness 30 .…”
Section: Electroencephalography and Cortical Activity In Sportmentioning
confidence: 99%
See 1 more Smart Citation
“…This rhythm was also studied as a marker of resources allocation during motor programming 32 . Beta oscillation (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30),on the other hand, has a central position in the treatment of sensorimotor information and serves as a functional link between different brain regions such as the pre-motor, motor (M1), and somatosensory (S1) cortex, the supplementary motor area, and the cerebellum 31 . Beta oscillation could play the role of a motor "binding" linking the different commands related to a global gesture as suggested for sensory awareness 30 .…”
Section: Electroencephalography and Cortical Activity In Sportmentioning
confidence: 99%
“…Mullen and colleagues 24 gave a different explanation of the meaning of HRV. They conducted a study on amateur golfers using a putting task performed with and without a concurrent distracting task.…”
mentioning
confidence: 99%
“…To date it has repeatedly been shown that adopting such a skill-focus of attention 1 impairs expert performance (e.g., Baumeister, 1984;Beilock & Carr, 2001;Gray, 2004;Gucciardi & Dimmock, 2008;Jackson et al, 2006;Liao & Masters, 2002;Mullen & Hardy, 2000;Mullen, Hardy, & Tattersall, 2005;. Therefore, Beilock and Gray (2007) concluded that there is compelling evidence that in the perceptual-motor domain choking is caused by explicit monitoring or conscious control of the execution of the skill.…”
mentioning
confidence: 99%
“…Repeated exposure to a stressful competitive situation has also been proposed to teach the athlete not only how to perform the skill properly but also how to execute it under pressure (Pijpers et al, 2003). Mullen, Hardy and Tattersall (2005) failed to find support for the conscious processing hypothesis, but suggested that multiple mechanisms, including both conscious processes and distraction effects, might affect performance in a complementary manner depending on the nature of the task.…”
Section: The Perspective Of Self-focus and Interference With Autonomomentioning
confidence: 99%